2008
DOI: 10.1210/jc.2007-1717
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analysis of Papillary Thyroid Cancer withPIK3CAAlterations in a Middle Eastern Population

Abstract: Context: Genetic aberration in phosphatidylinositol 3-kinase (PI3K)/AKT pathway has been detected in numerous and diverse human cancers. PIK3CA, which encodes for the catalytic subunit of p110␣ of PI3K, is amplified in some cases of papillary thyroid cancer (PTC). Mutations in the PIK3CA have also been identified in thyroid cancers and, although relatively common in anaplastic thyroid carcinoma, are uncommon in PTC.Objective: The objective of the study was to investigate genetic alterations like PIK3CA gene mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
154
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 167 publications
(166 citation statements)
references
References 29 publications
9
154
0
3
Order By: Relevance
“…18,19 splice junctions, were amplified and sequenced using primers and DNA samples from formalin-fixed paraffin-embedded blocks as described previously. 20 Primer 3 software was used to design the primers for exon 15 of BRAF (Table 2).…”
Section: Dna Isolationmentioning
confidence: 99%
“…18,19 splice junctions, were amplified and sequenced using primers and DNA samples from formalin-fixed paraffin-embedded blocks as described previously. 20 Primer 3 software was used to design the primers for exon 15 of BRAF (Table 2).…”
Section: Dna Isolationmentioning
confidence: 99%
“…28 For the study of UBE2C amplification, we used the bacterial artificial chromosome clone RP3-447F3, from Children's Hospital Oakland Research Institute (Oakland, CA). A UBE2C/centromere 20 ratio of 1.0 was considered normal, a ratio between 1.0 and 2.0 was considered as having UBE2C gains, and a ratio of Ͼ2.0 was considered as amplified.…”
Section: Fishmentioning
confidence: 99%
“…According to the current knowledge, leptin signaling pathway is mainly transduced by Janus activated kinase/signal transducers and activators of transcription (JAK/STAT), mitogen-activated protein kinase (MAPK), and phosphatidylinisitol-3 0 -kinase (PI3K) signaling pathways (Hegyi et al 2004). Previously, we have shown that aberrant PI3K/AKT signaling activation plays a role in Middle Eastern PTC pathogenesis (Abubaker et al 2008b). However, the expression of leptin receptors and the potential correlation between leptin receptors and PI3K/AKT activation have yet to be studied in the Middle Eastern population.…”
Section: Introductionmentioning
confidence: 99%